(untitled) (Architecture Image Studies, 2025)
This study examines the media coverage of ethnic tensions and violent events in Kosovo, focusing on the March 2004 riots and the Banjska attack of September 24, 2023. The main aim is to analyze how Albanian-language print and online media reported these events, with attention to both quantitative coverage and the language used. The research seeks to answer: How do media outlets in Kosovo cover interethnic conflicts, and to what extent does their reporting reflect bias or emotional framing? The study employs a content analysis methodology, reviewing articles from two major print newspapers, Koha Ditore and Epoka e Re, as well as digital coverage from Koha.net and the online version of Epoka e Re. Over selected periods, the total number of headlines and articles were counted, with a distinction made between content directly related to violent events and other topics. Findings indicate that while both print and online media reported extensively on the events, there were significant differences in the proportion of coverage devoted to ethnic violence. Moreover, the language used in reporting was often emotionally charged and, in some cases, potentially inciting interethnic tension, particularly during the 2004 riots. In contrast, coverage of the 2023 Banjska attack was largely accurate but included emotionally loaded terms. The study concludes that historical, cultural, and political factors, coupled with insufficient coordination with authorities, influence media practices, emphasizing the need for responsible journalism in ethnically sensitive contexts.